Pengaruh Return On Asset (ROA), Financing Deposit To Ratio (Fdr) Dan Return On Equity (ROE) Terhadap Capital Adequacy Ratio (CAR) Pada Bank Bukopin Syariah Periode 2018-2022 - Harahap, Annisa Fitriana; Rafidah, Rafidah; Alawiyah, Rabiyatul (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to examine the effect of Return On Asset, Financing Deposit to Ratio and Return On Equity simultaneously on Capital Adequacy Ratio (CAR) at Bank Bukopin Syariah for the period 2018-2022. The method in this research is quantitative. The type of research used is descriptive quantitative, namely the method of analyzing data using data in the form of numbers or values from the form of data then analyzed by adding information in the form of sentences to explain quantitative data. In this study, researchers collected data using the literature study method and the financial statements of Bank Bukopin Syariah in 2018-2022. The population used in this study is the financial statements of Bank Bukopin Syariah published in the Financial Services Authority (OJK). Sampling in this study using saturated sampling method. The results of this study are 1. There is a positive and significant effect of Return On Asset (ROA) on Capital Adequancy Ratio (CAR) at Bank Bukopin Syariah, 2. There is a positive and significant effect of Financing To Ratio (FDR) on Capital Adequancy Ratio (CAR) at Bank Bukopin Syariah, 3. There is a positive and significant effect of Return On Equity (ROE) on Capital Adequancy Ratio (CAR) at Bank Bukopin Syariah, 4. There is a positive and significant influence together between Return On Asset (ROA), Financing To Ratio (FDR), Return On Equity (ROE) on Capital Adequancy Ratio (CAR) at Bank Bukopin Syariah.